POLITENESS STRATEGIES USED BY ENGLISH NATIVE TEACHER: A CASE STUDY IN BILINGUAL PRE-KINDERGARTEN - Ni Kadek Ria Safitri; Gede Sutrisna (Universitas Warmadewa, 2022)
The study aimed at describing types of politeness strategies used in Bilingual Pre-Kindergarten in Denpasar-Bali. The research was designed as a qualitative study by employing four instruments which included the researcher as the main instrument, observation sheets, video recorder and interview guide. The finding showed that the English-Native-Speaker (ENS) teacher dominantly used positive politeness strategy in order to motivate the students in teaching and learning process with the closer relationship compared with bald on-record strategy, off-record strategy and negative politeness strategy. However, saying-nothing strategy (Don’t do the FTA) could not be found due to the age and the needs of the students in which they needed an active communication environment because it influenced their social-emotional development.